The Effect of Project Based Learning Model on Science Literacy Skills of Grade V Elementary School Students - Musfika Ali (Universitas Tidar, 2024)
This study aims to see the effect of project-based learning model in improving science literacy skills of elementary school students. This study used a non-equivalent control group research design with 56 samples divided into experimental and control groups. The instruments used were science literacy tests and observation sheets. The results of the pretest and posttest mean difference test of the control group using paired sample T-test. The results of data calculation obtained Sig. (2-tailed) of 0.000, p<0.05, so it can be concluded that there is a difference between the pretest and posttest results in the control group. The results of this test indicate that the treatment given to both the experimental and control classes has an effect on science literacy skills. It is concluded that the project-based learning model can effectively improve students' literacy skills based on the research conducted. The results of the analysis of science literacy skills of students whose learning uses project-based learning are higher than students who do not use project-based learning.